Comparison of continuous and intermittent incremental protocols for direct VO2 assessment - Cardoso, C.; Fernandes, R.; Magalhaes, J.; Santos, P.; Colaco, P.; Soares, S.; Carmo, C.; Barbosa, T.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming IX, 2003)
The purpose of this project was to compare two triangular protocols for VO2max assessment and minimum swimming velocity that elicits VO2max (vVO2max), one continuous, and one other intermittent. Result and Conclusion: Continuous and intermittent protocols provided similar results, both for VO2max and for vVO2max. The only significant difference was found on [LA-], but results were, nevertheless, very similar. This differences can be attributed to a systematic prevalence of glycolisis after each rest interval during the intermittent test, which was showed by high R values found before VO2 rise. We can conclude that both protocols are suitable for VO2max and vVO2max assessment in swimming.